Juvenile post dengue mucormycosis-reporting a rare entity with review of literature - Garg, Kavita N.; Raj, Vineet; Singh, Sujeet; Dwivedi, Ruby; Pandey, Praveen K.; Thahriani, Amit (International Journal of Research in Medical Sciences, 2025)
Invasive mucormycosis is a life-threatening fungal infection that most frequently occurs in patients with underlying comorbidities that impacts immune system function. It is an opportunistic and frequently fulminant fungal infection caused by a saprophytic organism belonging to class zygomycetes. These organisms are omnipresent and grow in their natural state on the variety of decaying organic materials. These organisms are present in the nasal passages and oral cavities of normal individuals. Here, we report a rare case of juvenile post dengue mucormycosis along with brief insight into the review of literature. Histopathological examination of the necrotic bone and overlying tissue was done in OPD in a juvenile patient who reported with purulent discharge and having a history of dengue. There were abundant PAS positive fungal hyphae. This case report will acquaint the oral care providers of a possible association of mucormycosis and dengue and highlight the importance of early diagnosis to optimize the treatment outcomes and prognosis in such cases. Mucormycosis is a rare opportunistic infection that spreads promptly and is life-threatening. Therefore, early diagnosis and prompt treatment is required to reduce the mortality and morbidity of this lethal infection.